2001
DOI: 10.4269/ajtmh.2001.65.848
|View full text |Cite
|
Sign up to set email alerts
|

Prospective case-control study of encephalopathy in children with dengue hemorrhagic fever.

Abstract: Abstract. We present a prospective case-control study of 27 serologically confirmed dengue hemorrhagic fever (DHF) patients with severe central nervous system symptoms. Dengue associated encephalopathy accounted for 0.5% of 5,400 patients admitted with DHF. The mortality rate among children with encephalopathy was 22%, with the survivors experiencing a complete recovery. Liver enzymes and bilirubin were significantly elevated in the study group. In analysis of the cerebrospinal fluid (CSF), reverse transcripta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
171
1
14

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(199 citation statements)
references
References 14 publications
5
171
1
14
Order By: Relevance
“…A partir de 1997, alguns estudos deram subsídios para tais hipóteses. A detecção da presença de anticorpos da classe IgM no LCR sugeriu que a infecção viral poderia ocorrer pela hemorragia ou pelas t rocas entre os vasos sanguíneos e as células nerv o s a s , o que possibilitaria a passagem de anticorpos do s o ro para o LCR 8 , podendo ser mediada por citocinas 9 . Embora o isolamento viral em LCR seja raramente referido na literatura, aventou-se a possibilidade da passagem viral pela barreira hematoencefálica durante a fase virêmica 8,9 .…”
unclassified
See 2 more Smart Citations
“…A partir de 1997, alguns estudos deram subsídios para tais hipóteses. A detecção da presença de anticorpos da classe IgM no LCR sugeriu que a infecção viral poderia ocorrer pela hemorragia ou pelas t rocas entre os vasos sanguíneos e as células nerv o s a s , o que possibilitaria a passagem de anticorpos do s o ro para o LCR 8 , podendo ser mediada por citocinas 9 . Embora o isolamento viral em LCR seja raramente referido na literatura, aventou-se a possibilidade da passagem viral pela barreira hematoencefálica durante a fase virêmica 8,9 .…”
unclassified
“…A detecção da presença de anticorpos da classe IgM no LCR sugeriu que a infecção viral poderia ocorrer pela hemorragia ou pelas t rocas entre os vasos sanguíneos e as células nerv o s a s , o que possibilitaria a passagem de anticorpos do s o ro para o LCR 8 , podendo ser mediada por citocinas 9 . Embora o isolamento viral em LCR seja raramente referido na literatura, aventou-se a possibilidade da passagem viral pela barreira hematoencefálica durante a fase virêmica 8,9 . Por meio de cultura de tecidos, utilizando células de neuroblastoma de ratos e de humanos, num modelo experimental, i d e ntificou-se, por imunofluorescência, a presença de antígenos virais no citoplasma e ao redor do núcleo, comprovando a existência de receptores virais do dengue envolvidos nos mecanismos de infecção do SNC 10 .…”
unclassified
See 1 more Smart Citation
“…2 Another study in Viet Nam found that 0.5% of children admitted for dengue hemorrhagic fever (DHF), which is a subset of severe dengue, had serologically confirmed DENV infection with encephalopathy, although rates of dengue-associated neurologic diseases as high as 21% have been reported. 3,4 The most efficient vector for DENV is Aedes aegypti, which is present in limited areas of the southern United States, but its current geographic distribution is not well-documented. 5 Ae.…”
mentioning
confidence: 99%
“…15,19 Both WNV and DENV can cause neuroinvasive disease. 17,18,[20][21][22][23][24] Some researchers have hypothesized that dengue endemicity might eventually produce sufficient cross-protective immunity to modulate WNV disease, resulting in a less severe clinical syndrome and making WNV difficult to detect in dengue-endemic countries. 19,25 These factors may explain why few cases of human WNV disease have been detected in Latin America and the Caribbean.…”
Section: Discussionmentioning
confidence: 99%